Sonographic Measurements of Intrahepatic Inferior Vena Cava, Liver Span, and Common Bile Duct: Normative Data and Respiratory Variability in Adult Nigerian Population - Mohammed Lawan Mohammed; Maryam Abba Goni; Ibrahim Abba Tijjani; Umar Hassan Umar; Abubakar Farate; Zara Mohammed Bata; Zara Baba Shettima; Ruqayyatu Abubakar Imam (West African Journal of Allied Health Sciences, 2026)
ABSTRACT Background: Population-specific reference values for sonographic measurements are essential for accurate clinical interpretation. While ultrasound is widely used in Nigeria, comprehensive normative data for intra-abdominal vascular structures, particularly the inferior vena cava (IVC), are limited for the Nigerian population. Objective: To establish normative reference values for intrahepatic IVC diameter, liver span, and common bile duct (CBD) diameter in healthy adults in North-Eastern Nigeria, and to evaluate their variations with respiration, age, and gender. Methods: A prospective study of 150 healthy adults comprising 78 males and 72 females, aged 19-70 years. B-mode ultrasound using a GE Logic S8 with 3-5MHz transducer was use to measure intrahepatic IVC diameter (transverse and longitudinal) during inspiration and expiration, liver span in mid-clavicular line, and CBD diameter. Collapsibility index was calculated. Statistical analysis included descriptive statistics, Student's t-test, and Pearson's correlation. Results: Mean age was 41.72±13.20 years. Normative values were: IVC transverse diameter (inspiration: 1.48±0.51 cm; expiration: 1.80±0.50 cm), IVC longitudinal diameter (inspiration: 1.43±0.53 cm; expiration: 1.71±0.51 cm), average IVC diameter (inspiration: 2.19±0.52 cm; expiration: 2.66±0.50 cm), IVC collapsibility index (21.4±8.7%), liver span (13.4±1.8 cm), and CBD diameter (inspiration: 0.22±0.04 cm; expiration: 0.30±0.07 cm). No significant gender differences were found in IVC dimensions (p>0.05). Weak positive correlation was found between age and liver span (r=0.177, p=0.030). Conclusion: This study establishes comprehensive normative sonographic values for intrahepatic IVC, liver span, and CBD in a Nigerian population. The IVC collapsibility index of 21.4% provides a reference for assessing intravascular volume status. These population-specific values will enhance the accuracy of ultrasound interpretation in clinical practice in Nigeria and similar populations.